EFFECTIVENESS OF PROBLEM BASED LEARNING ASSISTED BY POWERPOINT MEDIA ON STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITY IN JUNIOR HIGH SCHOOL - Rivaral, Etienne Rey; Lestariningsih, Desika (Perpendicular : Journal of Mathematics Education and Learning, 2025)
This study aims to examine the effectiveness of the Problem Based Learning (PBL) model assisted by PowerPoint media in mathematics learning for seventh-grade students at SMP Negeri 1 Puding Besar, particularly in improving students’ mathematical problem-solving ability. This study employed a pre-experimental research design using a one-group posttest-only approach. The participants consisted of 29 students from class VII.A. Data were collected through observation sheets, questionnaires, and a posttest. Data analysis was conducted using percentage analysis to evaluate student activities, learning outcomes, and learning attitudes. The results showed that the overall effectiveness of the PBL model assisted by PowerPoint media reached 82.7%, which falls into the very effective category. This effectiveness is supported by high levels of student activity, satisfactory learning completeness, and positive student responses. The findings indicate that the integration of PBL with visually supported PowerPoint media encourages active engagement and collaborative problem-solving, which are essential components in developing students’ mathematical problem-solving skills.